2017
DOI: 10.1097/mcg.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endoscopic Resection and Minimally Invasive Esophagectomy in Patients With Early Esophageal Cancer

Abstract: ER achieves the same positive results as MIE in the treatment of early esophageal cancer and is associated with a lower complication rate, a shorter recovery time, and a similar survival rate. However, multiple ER procedures were required for several patients in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…ESD is associated with favorable results in terms of long term outcomes [26]. We verified these results in our study.…”
Section: Discussionsupporting
confidence: 88%
“…ESD is associated with favorable results in terms of long term outcomes [26]. We verified these results in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Esophagectomy is the standard treatment for EC. Radiotherapy is an effective treatment option to cure or control EC (Jin et al, 2017). Targeted therapy is a key step in the development of individualized treatment for EC.…”
Section: Introductionmentioning
confidence: 99%
“…One study compared the two treatment modalities and found similar rates in the treatment of early esophageal cancer (R0 resection rate 94.9% vs 97.5%, P > 0.05), 3-year survival (96.6% vs 97.5%, P > 0.05), 4-year survival (91.5% vs 90%, P > 0.05) and local recurrence ( P > 0.05)[33]. However, EET was superior with fewer complications (11.8% vs 32.5%, P > 0.05), shorter operative time (74 ± 23 min vs 298 ± 46 min), hospital LOS ( P < 0.001) and recovery time compared to MIE[33]. Therefore, EET is increasingly used as it is cost effective, has minimal morbidity and mortality with excellent long-term survival comparable to esophagectomy.…”
Section: Outcomes: Eet Versus Esophagectomymentioning
confidence: 99%